A Guarda Nacional na fronteira Oeste do Império do Brasil (1850-1864) - Silva, Jonh Érick Augusto da (2011)
The nineteenth century is characterized as a historical period in which great changes occurred in the political, economic, social and cultural fields in the Empire of Brazil. One of the many changes in 1831 resulted in the creation of the paramilitary militia composed of citizens called the National Guard. This research aims to analyze the reform that occurred in that institution in 1850, being the temporal cut the eve of war with Paraguay in 1864, in other words, we are interested in understanding the National Guard during the period known in Brazilian historiography as Apogee of the Empire. Our focus is on the province of Mato Grosso, a region characterized by its borders with the Republics of Paraguay and Bolivia. The work is based on sources enrolled specially in the Public Archive of Mato Grosso, namely: Reports, speeches and messages of presidents of the province, Ministry of Justice reports, memorandums sent by the provincial government for National Guard commanders such as for the Ministry of Justice, and the epistolary documents recorded in the books of correspondence.